(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
The addition of carbon nanotube (CNT) to the solder alloy has gained the attention due to its beneficially improve the mechanical properties of the solder alloy. Because of the miniaturization progress of electronic component, micromechanical properties of solder joint need to be focused instead of conventional mechanical properties. In this study, micromechanical properties, and deformation behaviour of SAC305 solder joints with the different CNT doping (weight percentage of 0.01, 0.02, 0.03 and 0.04) were investigated. Localized micromechanical properties included hardness, reduced modulus and stress exponent were determined via nanoindentation approach. Microstructural analysis was performed via optical microscope and field emission scanning microscope (FESEM). Doping of CNT in the SAC305 solder matrix changed the microstructure phase distribution. It was found that, doping of CNT, increase the near eutectic phase and decrease the primary b-Sn phase area. Furthermore, hardness values of SAC305 solder joint increased with increasing of CNT doping weight percentage. Hardness values of SAC305 solder joint increase about 7 - 40% with the doping of CNT from 0.01 wt. % to 0.04 wt. %. However, localized reduced modulus and stress exponent show random values and no correlated trend with CNT doping were observed. Random values trend of stress exponent revealed that, SAC305 solder joint with the CNT doped involved the combination of deformation mechanism. This is due to the response of phase and CNT in the solder matrix to the localized indentation. In conclusion, a localized approach to hardness properties influenced by the CNT doping weight percentage.